Indian Automobile Companies' Financial Efficiency Measurement: An Investigation using Super Efficiency and Factor Analysis. (March 2014) - Ghosh, Arijit; Agarwal, Baishali; Bandyopadhyay, Gautam; Choudhuri, Kripasindhu
This article investigates the Super Efficiency of Indian Automobile Companies. Attempts are made to study the efficiency of fund utilization, both debt and equity, by relating returns to the respective stakeholders supplying the funds, as well as efficiency of working capital in generating sales using publicly available financial data of these companies. The Data Envelopment Analysis is employed to estimate the financial efficiency of each company in comparison with other companies of automobile sector with the help of different efficiency scores keeping in mind different aspect of operations. Then Super Efficiency Model is applied on most efficient companies to find out the super efficient company. The different efficiency scores thus obtained are reduced into a single most explanatory score with the help of factor analysis. Based on efficiency measurement and factor score, the companies are then sorted. This gives us clear idea regarding performance of different companies for the stipulated time horizon.